The “Social Gaze Space”: A Taxonomy for Gaze-Based Communication in Triadic Interactions - Jording, Mathis; Hartz, Arne; Bente, Gary; Schulte-Rüther, Martin; Vogeley, Kai (Frontiers in Psychology, 2018)
Humans substantially rely on nonverbal cues in their communication and interaction with others. The eyes represent a “simultaneous input-output device”: While we observe others and obtain information about their mental states (including feelings, thoughts, and intentions-to-act), our gaze simultaneously provides information about our own attention and inner experiences. This substantiates its pivotal role for the coordination of communication. The communicative and coordinative capacities – and their phylogenetic and ontogenetic impacts – become fully apparent in triadic interactions constituted in its simplest form by two persons and an object. Technological advances have sparked renewed interest in social gaze and provide new methodological approaches. Here we introduce the ‘Social Gaze Space’ as a new conceptual framework for the systematic study of gaze behavior during social information processing. It covers all possible categorical states, namely ‘partner-oriented’, ‘object-oriented’, ‘introspective’, ‘initiating joint attention’, and ‘responding joint attention’. Different combinations of these states explain several interpersonal phenomena. We argue that this taxonomy distinguishes the most relevant interactional states along their distinctive features, and will showcase the implications for prominent social gaze phenomena. The taxonomy allows to identify research desiderates that have been neglected so far. We argue for a systematic investigation of these phenomena and discuss some related methodological issues.